An exploratory analysis of source integration in post-secondary L1 and L2 source-based writing - Doolan, Stephen M. (English for specific purposes (New York, N.Y.), 2021)
Post-secondary students across the curriculum are commonly required to integrate source text material into their academic writing. While writing from multiple sources occurs frequently in higher education (Rosenfeld et al., 2001) and is a cognitively demanding task, few studies have investigated the types of source integration used by L1 and L2 writers entering post-secondary, first-year composition (Cumming et al., 2016). This study compares L1 and L2 in-class writing from multiple sources to quantitatively investigate similarities and differences in (1) use of various types of source integration (e.g., citations, paraphrases, direct quotes), and (2) use of ideational units. The writing was also analyzed qualitatively to follow up on select patterns from the quantitative findings. Results indicated that despite lower holistic writing quality scores, the L2 writing, in certain respects, demonstrated more responsible use of various types of source integration compared to L1 writing. The analysis also revealed very low frequencies of synthesis writing for both L1 and L2 writing. Finally, the findings are discussed as they relate to simplified versus elaborative integration of source material in student writing. •L1 writers achieved significantly higher holistic quality scores than the L2 writers.•L2 writers demonstrated more responsible orientation to source texts in certain respects.•Both L1 and L2 writers produced very few instances of synthesis writing.•Relative to L2 writing, L1 writing displayed more transformation of source ideas.